Aniruddha - Temples of India Project Team (Jio Institute, 2024)
The adhisthana has depictions of various Hindu gods and goddesses framed within elaborately carved panels. This panel depicts lord Vishnu seated on his mount Garuda. Lord Vishnu is depicted as chaturbahu (with four hands). In his rear right hand, he is carrying the gada (mace), named Kaumodaki, and in his rear left hand, the chakra (discus) named Sudarshana, while the front two hands are broken. A pair of vidhyadharas (knowledge bearers) are seen flying on the top corners, showering floral garlands. Two male attendants (seated) and two female attendants (standing) flank Vishnu on either side. The faces, feet, and hands of the figures are broken and their attributes are not clear.